Implementasi Kebijakan Pengembangan Anak Usia Dini Holistik Integratif (PAUD HI) di Kota Bogor - Citra Andita; Dini Gandini Purbaningrum (Jurnal Hukum dan Sosial Politik, 2024)
This article discusses the implementation of the Integrative Holistic Early Childhood Development Policy in the City of Bogor. This research aims to describe the implementation of HI PAUD policies in Bogor City. This research method is descriptive with a qualitative approach. The data collection techniques used were observation, interviews and documentation. This research uses the Policy Implementation theory according to George C. Edward III, in which there are four indicators to assess the success of a policy, namely (1) Communication, communication has been carried out, but has not been optimal because socialization has not been carried out thoroughly to every PAUD unit; (2) Resources, in terms of the quantity of human resources, are inadequate, causing the delivery of information to be less effective, the limited budget means that the Bogor City Education Office only helps a little in terms of facilities for PAUD units; (3) Disposition, the officers have the knowledge and ability as a form of commitment in implementing the HI PAUD policy, but incentives cannot be given to PAUD Unit managers due to budget limitations; (4) Bureaucratic structure, in implementing HI PAUD policies, implementers only refer to applicable regulations and make adjustments to the conditions of each school. The suggestion from this research is that socialization must be carried out massively, it would be better for the Bogor City Education Office to add personnel, maximize the use of social media and provide incentives to PAUD unit managers.